Akad - akad dan Produk Produk Perbankan Syariah - Nurfazilah Nurfazilah; Ayu Silfia; Ilham Ilham (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This scientific paper examines various types of contracts and products in Islamic banking based on the principles of Islamic law. Islamic banks have a mission not only as financial intermediary institutions, but also as drivers of the values ​​of social justice, transparency, and blessings. This study aims to examine the implementation of Islamic contracts such as mudharabah, musyarakah, murabahah, ijarah, wakalah, and product development based on the principles of tabarru' and tijarah. The methods used are literature studies and descriptive analysis of DSN-MUI fatwas, OJK regulations, and empirical practices of Islamic banking in Indonesia. The results of the study indicate that although the implementation of contracts has referred to Islamic principles, there are still legal challenges, such as dualism of the legal system, disharmony of fatwas, and limited human resources. Therefore, synchronization of regulations and strengthening of Islamic literacy are needed to ensure sustainable Islamic compliance.